Fundamental Analysis in Investment Decision Making on the Indonesia Stock Exchange Accelerated Board - Nurul Afifah; Maya Sari; Andrieta Shintia Dewi; Ferry Arfiansyah (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Fundamental analysis is one of the considerations for investors to invest in a company. The study aims to identify the appropriate investment choices for companies listed on the Indonesian Stock Exchange accelerated board. By calculating, examining, and deriving inferences from the financial records of the sample organizations, this research employs a quantitative descriptive technique. Three companies in the acceleration board that meet specified criteria make up the research sample. The research data is in the form of financial reports for the three years from 2019 to 2021. The results show that PT Panca Anugrah Wisesa Tbk. has the greatest average ROA, PT Prima Globalindo Logistik Tbk has the highest average CR, PT Prima Globalindo Logistik Tbk k. Offers the highest average DAR value, and the highest average TATO value at PT Prima Globalindo Logistik Tbk. Based on these findings, it is possible to infer that the best investment decision in PT Prima Globalindo Logistik Tbk.